Green approaches to biocomposite materials science and engineering - Verma, Deepak d 1983-; Jain, Siddharth 1984-; Zhang, Xiaolei 1986-; Gope, Prakash Chandra (Advances in Chemical and Materials Engineering (ACME) Book Series, 2016)
This book explores timely research on the various available types of natural fibers and the use of these fibers as a sustainable alternative to synthetic fibers and polymers by emphasizing research-based solutions for sustainability across various industries--Provided by publisher